HUBUNGAN SELF EFFICACY DENGAN ADAPTASI STRESS PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RSUD WALED KABUPATEN CIREBON - Ica Wahyuni; Nonok Karlina; Citra Setyo Dwi Andhini (Jurnal Kesehatan Mahardika, 2019)
Patients with chronic kidney failure each year experience an increase of 3.8 percent. To overcome kidney failure, hemodialysis therapy is needed. But patients undergoing hemodialysis will experience problems such as discomfort, increase stress and affect quality of life. To reduce these problems, intervention is needed to give self efficacy to patients, based on this it will also affect the stress adaptation of patients undergoing hemodialysis.Purpose of this research was to knew correlation of self efficacy with stress adaptation on chronic kidney failure patients that have hemodialysis in the Waled Hospital of Cirebon.Design of this research was descriptived correlating with cross sectional approach. Sample of this research using purvosive sampling amounted 99 respondens. Instruments used in the form of questionnaire. Data analysis using Spearman- rank test. The place of research at waled hospital in the Cirebon.The results showed that the majority of self-efficacy carried out in the hemodialysis room of Waled Hospital in Cirebon District was mostly in the low category of 90 (90.9%) and stress adaptation was mostly in the very severe category 54 (54.5%). The results of the Spearman rank test 0.000 ( P Value = 0.000 ; α.= 0.05 ; r = 0.546 ).show that H0 is rejected. Conclusion of this research there was a correlation of self efficacy with stress adaptation on chronic kidney failure patients that have hemodialysis in the waled hospital of Cirebon.